Direct and moderating effects of personality on stigma towards mental illness - Yuan, Qi (BMC Psychiatry, 2018)
BACKGROUND: While many studies have explored the concept and correlates of stigma towards individuals with mental illness, few have investigated the role of personality in this process. In the current study, we firstly examined the relationship between personality and stigma towards mental illness; and then explored the moderating effects of personality traits on the relationship between contact experience/s and stigma. METHODS: Participants were recruited from public medical (N = 502) and nursing schools (N = 500) from April to September 2016 in Singapore for this cross-sectional survey, and they were randomly assigned to a vignette describing one of the following mental disorders: major depressive disorder, obsessive compulsive disorder, alcohol abuse, schizophrenia, and dementia. Stigma was measured by the ‘Personal and Perceived scales of the Depression Stigma Scale’ and the ‘Social Distance Scale’. These scales together had a 3-factor structure based on a previous national study in Singapore, namely ‘weak-not-sick’, ‘dangerous/unpredictable’ and ‘social distance’. Personality was measured by the 20-item short form of the International Personality Item Pool-five factor model measure. RESULTS: Regression suggested agreeableness and openness to experience were negatively associated with all three domains of stigma. ‘Weak-not-sick’ and extraversion were positively associated; and ‘social distance’ was positively associated with higher scores on conscientiousness and neuroticism. Both close- and non-close contact were associated with more positive attitudes towards mental illness among the participants. Openness to experience moderated the relationships of close contact experience with ‘weak-not-sick’ and ‘dangerous/unpredictable’, but in different directions. The association between close contact and ‘social distance’ were moderated by agreeableness. CONCLUSIONS: Unlike non-close contact experience, close contact with people with mental illness worked differently on stigma for individuals with different personality traits. Future studies are needed to further explore the underlying mechanisms for such differences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12888-018-1932-3) contains supplementary material, which is available to authorized users.